IMPOSTER SYNDROME: Why Nurses Question their Competence - Stephanie John (The Nursing times, 2019)
“Impostor syndrome” is described as intense feelings of fraudulence and self-doubt in the face of success. The phenomenon was first defined by Clance and Imes (1978), who found that many high achieving women doubt their expertise and feel they have fooled others into believing they are more capable than they are. Success is deemed to be a result of luck, hard work or fooling others, rather than ability. Imposter syndrome is common and is said to have been experienced by seventy percent of the population at some time in their lives. It is particularly common in environments where intellect is central to success. It is unsurprising that the Imposter syndrome therefore thrives in academic contexts.Imposter syndrome therefore often appears when Nurses transition from nursing practice into the world of academia and nurse education. It is however often common among newly qualified Nurses and more experienced nurses who choose to progress within the field. Despite the context, it is known to have destructive effects. It is hoped that this article will resonate with readers, promote awareness and understanding of Imposter Syndrome.